Institucionalização dos princípios do sistema único de saúde (SUS): um estudo de caso do conselho municipal de saúde de São João Del Rei (MG) - Moraes, Paula Belgo (2016)
This study had the objective of verifying how the principals of the Unified Health System (SUS) were institutionalized in the assemblies and deliberations of the Municipal Health Council (MHC) of São João Del-Rei, Minas Gerais, Brazil, in 2015. By means of a reflexive theoretical-empirical study, we sought to describe, analyze, identify and explain how the institutionalization of these principals occurred in the sphere of the Health Council. Being the Councils a sphere of participation and social control, and relying on the participation of actors from many segments of the interest of public health, we believe this space is a good indicator of how the principals of SUS are being institutionalized. In this first part of this study, we conducted a bibliographical review concerning health public policies, social participation and institutionalism. Later, we conducted an empirical research by means of non-participant active observation, accompanying the meetings of MHC of São João Del-Rei during 2015. We focused on the observation of the principals of the SUS and how these were institutionalized in this participative space. With these observations, a semistructured interview was conducted with the actors assiduous of the meetings and of many segments during the period of the research. By means of this research, we identified that, despite the theorization of the principals not being clear to all actors, the use of the concepts in the assemblies and deliberations exist. Individually, the actors have difficulty in recognizing the principals in the actions performed by the MHC, but are capable of recognizing and pointing them out in the actions, deliberations and general considerations. In conclusion, despite the weaknesses identified in the participative process, the principals of the SUS permeate the assemblies by the agenda taken to the plenary of the Council, as well as the deliberations and speeches of the councilmen.